A radiologic morphometric study of sellar, infrassellar and parasellar regions by magnetic resonance in adults - Yamashita, Seizo [UNESP] (2014)
To evaluate variations of some anatomic structures of sellar and parasellar regions and their possible differences between genders and age groups. Magnetic resonance images (MRI) of 380 patients were performed to analyze the dimensions of the sphenoid sinus, pituitary gland, optic chiasm, intra-cavernous carotid distances, distance between columella nasal - sphenoid sinus; and columella nasal-pituitary gland. The patients age ranged between 20 and 80 years (mean age 48 years). The study included 235 females (mean age 53 years) and 145 males (mean age 40 years). The transverse length of the pituitary, the inter-carotid distance and the height of the pituitary were similar between genders and age groups. The width and height of the optic chiasm showed differences only between females of different ages. Males presented greater distances between nasal columella and sphenoid sinus. The most common type of pneumatization of the sphenoid sinus was the sellar, and depending on the age group, sphenoid sinus was larger in males than females. The anatomy of the Sellar and parasellar regions is complex and varies widely within the normal range. They are a small area, rich in anatomical details affecting multiple physiological systems in the body and, therefore, have great importance in several medical fields. A better understanding of these complex structures is essential in clinical diagnosis and treatment of disease.